Establishment of Cholangiocarcinoma Organoids from Long-Term Frozen Tissues - Suntiparpluacha, Monthira; Chanwat, Rawisak; Limsrichamrern, Somchai; More-krong, Pimkanya; Srifa, Suchada; Kongsri, Kamonchanok; Aroonpruksakul, Satinee; Sathirareuangchai, Sakda; Sampatavanich, Somponnat; Okada, Seiji; Jirawatnotai, Siwanon (Journal of Basic and Applied Pharmacology, 2022)
Patient-derived tumor organoids (PDOs) are cultures of tumor cells that can be derived from individual patients, which recapitulate morphological and genetic features of the original tumor, making PDOs a very valuable tool for drug testing, biomarker and mechanism of disease research. However, the ability to make organoids consistent and in large numbers poses a technical challenges to overcome. Currently, cholangiocarcinoma (CCA) PDO is a scarce resource, because of the low number of fresh tissue available to research institutes, impeding the research to find a cure for this disease. Our work described establishments of CCA-PDOs from long-term frozen CCA tissues, and characterizations of the CCA-PDOs. We also performed drug testing on the CCA-PDOs using several drugs indicated in the standard regimens for CCA treatment. We were successful at establishing CCA-PDOs from 3-month-old, and 3-year-old frozen tissues, and found that these CCA-PDOs reserve the expression of pertinent proteins histologically specific to CCA. The CCA-PDO generated from the long-term frozen tissues also displayed qualities such as, organoid shape, protein expression, and drug response profiles indistinguishable from that of the CCA-PDO prepared from non-frozen fresh tissue. They can also be expanded and stored. Therefore, we conclude that the long-term preserved CCA tissue is capable to revive and preserve the characteristics of the original tissue, and suitable for precision oncology research. This procedure would allow the gathering of specimens from remote locations and enables establishment of reliable larger CCA-PDO collections.